Snowbreeder 5: a Micro-CT device for measuring the snow-microstructure evolution under the simultaneous influence of a temperature gradient and compaction - MAREIKE WIESE; MARTIN SCHNEEBELI (Journal of Glaciology, 2017)
The instrumented sample holder Snowbreeder 5 is used to investigate the simultaneous influence of settlement on temperature-gradient snow metamorphism in time-lapse micro-computed tomography experiments. So far, experiments have only been done on temperature-gradient snow metamorphism without settlement or settlement under isothermal conditions. With the new device we can impose a constant temperature gradient on a snow sample and induce settlement by placing a passive load on top of the snow sample. The weight of the load can be varied, simulating various snow heights on top of the snow sample. Snow-temperature measurements on the passive load are possible due to wireless data transfer via Bluetooth. The temperature gradient is set by controlling the air temperature inside the computer tomograph and by a Peltier element at the bottom of the snow sample. First experiments under isothermal conditions and a constant temperature gradient of 43 K m−1 showed that the settlement was reduced to almost half as soon as a temperature gradient was applied under otherwise almost equal snow conditions. The compactive viscosity in the isothermal experiment was in the range of literature values.